Prior infection with a nonpathogenic chimeric simian-human immunodeficiency virus does not efficiently protect macaques against challenge with simian immunodeficiency virus. - Letvin, N L (1995)
Prior infection with a nef-deleted simian immunodeficiency virus (SIV) protects macaques not only against a homologous pathogenic SIV challenge but also against challenge with a chimeric SIV expressing a human immunodeficiency virus type 1 env gene (SHIV). Since this SHIV is itself nonpathogenic, we sought to explore the use of a nonpathogenic SHIV as a live, attenuated AIDS virus vaccine. Four cynomolgus monkeys infected for greater than 600 days with a chimeric virus composed of SIVmac 239 expressing the human immunodeficiency virus type 1 HXBc2 env, tat, and rev genes were challenged intravenously with 100 animal infectious doses of the J5 clone of SIVmac 32H, an isolate derived by in vivo passage of SIVmac 251. Three of the four monkeys became infected with SIVmac. This observation underlines the difficulty, even with a live virus vaccine, in protecting against an AIDS virus infection.